2018
DOI: 10.1089/jmf.2017.4116
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of a Mixture of Lactic Acid Bacteria and Sodium Butyrate in Atopic Dermatitis Murine Model

Abstract: Atopic dermatitis is a chronic and recurrent inflammatory skin disease. Recently, probiotics have been shown to suppress allergic symptoms through immunomodulatory responses. In the present study, combinatorial effects on allergic symptoms were identified in BALB/c mice fed with a mixture of four species of probiotics, Bifidobacterium lactis, Lactobacillus casei, Lactobacillus rhamnosus, and Lactobacillus plantarum, and sodium butyrate. Following sensitization with whey protein, the mice were challenged and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 46 publications
0
25
1
Order By: Relevance
“…Endophytic microbial-derived butyric acid in A. arborescens leave could exert anti-cancerous effects by several mechanisms, highlighting the importance for health maintenance [32] . Regulation of the epigenome in particular inhibition of histone deacetylases, [33] demonstrated that probiotics mixture and sodium butyrate increased Th1 and Treg cell differentiation in mesenteric lymph nodes and spleen tissues in mouse model. These results suggest that the probiotic mixture and sodium butyrate can prevent and alleviate allergic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic microbial-derived butyric acid in A. arborescens leave could exert anti-cancerous effects by several mechanisms, highlighting the importance for health maintenance [32] . Regulation of the epigenome in particular inhibition of histone deacetylases, [33] demonstrated that probiotics mixture and sodium butyrate increased Th1 and Treg cell differentiation in mesenteric lymph nodes and spleen tissues in mouse model. These results suggest that the probiotic mixture and sodium butyrate can prevent and alleviate allergic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes and Bacteroidetes were the two most abundant bacterial phyla in the gut microbiota community. A common metabolite of Gram-positive Firmicutes, butyrate, is identi ed as an antiin ammatory molecule, which help to impede bacterial transport across the intestinal epithelial wall and increase the rate of tight junction formation, thereby maintaining the healthy gut environment [23,24]. The aberrant proliferation of Gram-negative Bacteroidetes contributes to the production of lipopolysaccharides (LPS) and then induces the low-grade in ammation by activating Toll-like receptor 4 (TLR-4) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes and Bacteroidetes were the two most abundant bacterial phyla in the gut microbiota community. A common metabolite of Gram-positive Firmicutes, butyrate, is identi ed as an antiin ammatory molecule, which help to impede bacterial transport across the intestinal epithelial wall and increase the rate of tight junction formation, thereby maintaining the healthy gut environment [24,25]. The aberrant proliferation of Gram-negative Bacteroidetes contributes to the production of lipopolysaccharides (LPS) and then induces the low-grade in ammation by activating Toll-like receptor 4 (TLR-4) [26].…”
Section: Discussionmentioning
confidence: 99%